A specific protein carboxyl methylesterase that demethylates phosphoprotein phosphatase 2A in bovine brain. - Lee, J (1996)
Phosphoprotein phosphatase 2A (PP2A) is one of the four major protein serine/threonine phosphatases found in all eukaryotic cells. We have shown that the 36-kDa catalytic subunit of PP2A is carboxyl methylated in eukaryotic cells, and we have previously identified and purified a novel methyltransferase (MTase) that is responsible for this modification. Here, we describe a novel protein carboxyl methyl-esterase (MEase) from bovine brain that demethylates PP2A. The enzyme has been purified to homogeneity as a monomeric 46-kDa soluble protein. The MEase is highly specific for PP2A. It does not catalyze the demethylation of other protein or peptide methylesters. Moreover, MEase activity is dramatically inhibited by nanomolar concentrations of okadaic acid, a specific inhibitor of PP2A. From these results, we conclude that PP2A methylation is controlled by two specific enzymes, a MTase and a MEase. Since PP2A methylation is highly conserved in eukaryotes ranging from human to yeast, it is likely that this system plays an important role in phosphatase regulation.